Big-five personality as a moderating variable in the relationship of CEO's perception and the compensation received toward CEO's desire to leave the company voluntarily - Lindrianasari, Lindrianasari (Journal of Economics, Business, and Accountancy Ventura, 2015)
The study aims to obtain empirical evidence for the effect of personality on the impact of compensation received by CEO in Indonesia toward CEO voluntary turnover. This study uses two sources of data, primary and secondary. The research population consists of all president directors (as a proxy of the CEOs) of companies listed on the Indonesia Stock Exchange. The data on CEO turnover were collected manually by tracing the names of the Director stated on the company's annual report. To determine whether CEO turnover was involuntary or coercive, this research examined the growth of the company in which the CEO turnover occurred after the CEO had served a minimum of three consecutive years. Test result on the relationship between com-pensation and turnover indicates that compensation is not strong enough to explain voluntary CEO turnover. Only the control variables included in the model (earnings, returns and ROA) can explain statistically the relationship between compensation and turnover. The result of these two tests (hypothesis one and two) indicates that com-pensation is not strong enough to explain voluntary turnover.